Self-organization of swimmers drives long-range fluid transport in bacterial colonies - Haoran Xu (Nature Portfolio, 2019)
Motile and non-motile subpopulations often coexist in bacterial communities. Here, Xu et al. show that motile cells in colonies of common flagellated bacteria can self-organize into two adjacent motile rings, driving stable flows of fluid and materials around the colony.